(untitled) (Modern education and development, 2025)
The rapid advancement of medical technologies has led to a growing demand for highly skilled professionals who can effectively utilize these technologies in clinical settings. Medical technology education plays a pivotal role in ensuring that future healthcare professionals possess the necessary knowledge and skills to meet the challenges of modern medicine. This article explores the key disciplines essential in the education of medical technologists and highlights their significance in enhancing the quality of healthcare services.